Network Neutrality and Network Management Regulation: Quality of Service, Price Discrimination, and Exclusive Contracts - Nicholas Economides; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2011)
We compare four approaches to network neutrality and network management regulation in a two-sided market model: (i) no variations in Quality of Service and no price discrimination; (ii) variations in Quality of Service but no price discrimination; (iii) variations in Quality of Service and price discrimination but no exclusive contracts; and (iv) no regulation: the network operator can sell exclusive rights to content providers. We compare the equilibrium outcomes explicitly accounting for dynamic incentives to invest in improving the Quality of Service offered to each content provider. We provide a ranking Quality of Service and network operator profits across regimes.
Keywords: C63; D40; D42; D43; L10; L12; L13; 330; Network neutrality; Internet price discrimination; Exclusivity; Quality of Service; Network management; Congestion; AT&T; Verizon; Google; Internet; Netzregulierung; Dienstleistungsqualität; Marktstruktur; Preisdifferenzierung